2019
DOI: 10.1093/ntr/ntz161
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Nicotine Without Misleading the Public: Descriptions of Cigarette Nicotine Level and Accuracy of Perceptions About Nicotine Content, Addictiveness, and Risk

Abstract: Significance The public incorrectly believes very low nicotine content (VLNC) cigarettes are less carcinogenic than current cigarettes, a belief associated with lower motivation to quit under a VLNC standard. We examined how different descriptions of the nicotine level in VLNC cigarettes affect the accuracy of the public’s perceptions about nicotine content, addictiveness, and cancer risk. Methods Participants were a national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Another possible reason for the observed disconnect is that the nicotine level of LNC cigarettes was never quantified in the survey measure. Recent studies have shown that stating “95% of the nicotine would be removed”, which reflects levels of nicotine in LNC cigarettes versus conventional cigarettes, results in more accurate perceptions of the addictiveness of LNC cigarettes [ 79 ]. Another observed misperception is that over 60% of respondents indicated that it is the nicotine in cigarettes causing cancer, which is consistent with prior studies including one among U.S. physicians [ 31 , 32 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason for the observed disconnect is that the nicotine level of LNC cigarettes was never quantified in the survey measure. Recent studies have shown that stating “95% of the nicotine would be removed”, which reflects levels of nicotine in LNC cigarettes versus conventional cigarettes, results in more accurate perceptions of the addictiveness of LNC cigarettes [ 79 ]. Another observed misperception is that over 60% of respondents indicated that it is the nicotine in cigarettes causing cancer, which is consistent with prior studies including one among U.S. physicians [ 31 , 32 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…After viewing the warnings and responding to survey items, participants completed two additional experiments (30,31) and answered demographic items. Participants received $2.20 for completing the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Another recent study examined how different ways of describing nicotine reduction in cigarettes affect perceptions of VLNCs. 14 The description ranged from very simple to very detailed by adding numerical reduction (removal of “95% of the nicotine”), a pictograph, and the words “nearly nicotine-free” alone and in combination. The study found that descriptions including the numeric information (95%) were more effective at conveying to smokers and non-smokers that VLNCs contain less nicotine and are less addictive than current cigarettes (which are correct beliefs) but also fostered perceptions that VLNCs are less harmful to smoke (incorrect belief).…”
Section: Discussionmentioning
confidence: 99%
“…So far, very little research has examined different ways to describe nicotine reduction in cigarettes and how those might influence smokers’ perceptions and behavior. 11,13,14 Most of this extant research has been conducted in the context of experimental studies where smokers were given VNLCs and told that these cigarettes contained either “very low nicotine” or “average nicotine.” 13 More participants were interested in quitting when being informed the only cigarettes for purchase in the future were “very low nicotine” cigarettes rather than “average nicotine” cigarettes. 11 However, these studies did not measure other behavioral intentions, such as likelihood of switching or dual use, nor did they assess the framing of the nicotine reduction.…”
Section: Introductionmentioning
confidence: 99%